Ta’līm al-Lughah al-’Arobiyyāh bi Istīkhdam al-Jarōid Litanmiyati Mahāroh al-Qiro’ah Fīy Madrosah Al-Kholīlahا BiJakārta al-Syarqiyyah - Segaf Baharun; Ubaidillah (Lughawiyyat)
The background in this thesis is learning Arabic by using magazines to improve reading skills at Madrasah Kholilah, East Jakarta. The main purpose of this learning is so that students are able to understand the basic rules of the Arabic language systematically, as well as understand and have the ability to read Arabic texts in accordance with the rules that have been set. Therefore, the researcher wants to study Arabic learning by using magazines to improve reading skills at Madrasah Kholilah, East Jakarta, related to planning, implementation, problems, and solutions. The focus of this research are: 1) How to plan the use of learning Arabic by using magazines to improve reading skills at Madrasah Kholilah, East Jakarta?, 2) How to apply the use of learning Arabic by using magazines to improve reading skills at Madrasah Kholilah, East Jakarta ?,